Career patterns in self-employment and career success - Koch, Michael; Park, Sarah; Zahra, Shaker A. (Journal of Business Venturing, 2021)
A substantial body of research examines entry into and exit from self-employment. However, little is known about the career patterns of the self-employed, their transitions into and from self-employment and the success associated with different patterns of their careers. To address these issues, we examine the career patterns of individuals with self-employment experience and their relationship to objective and subjective career success using data from the German Household Panel (SOEP). Our results show that persistent self-employment careers have higher gross labor income and exhibit higher job and life satisfaction than all other self-employment career patterns.